The impact of lifestyle on male fertility - review - Wiklińska, Agata; Śliwińska, Martyna; Wójtowicz, Katarzyna; Walczak, Agata; Jaroń, Aleksandra; Piątkowska, Karolina; Niegowska, Wiktoria; Wirkijowski, Jakub; Gajek-Flanczewska, Wiktoria; Flanczewski, Sebastian; Woźniak, Paulina; Kidacki, Kajetan (Quality in Sport, 2024)
Introduction and aim of study: The World Health Organization defines infertility as the disease of reproductive system defined by the failure to achieve a pregnancy after 12 months or more of regular unprotected sexual intercourse. It is estimated that 30% of infertility is due to the male factor, and 25% to the coexistence of the male and female factors. The purpose of this review study was to provide an overview of lifestyle risk factors for male infertility and their impact on the organism. Materials and methods: The authors conducted an extensive review of articles available in PubMed, Google Scholar, UpToDate, Science Direct, and Cochrane databases. The keywords infertility, lifestyle, testosterone, men were the basis of the review. Results: Leading an unhealthy lifestyle can significantly impact male fertility. The function of the reproductive system can be affected by inadequate body weight, as well as leading a sedentary lifestyle, using stimulants or anabolic steroids. They not only affect the endocrine system by disrupting steroidogenesis and spermatogenesis but may also directly damage sperm. This leads to impaired semen quality and increases the risk of recurrent pregnancy loss and poor pregnancy outcomes. Conclusion: Lifestyle significantly affects male fertility. A balanced diet, adequate physical activity and avoidance of stimulants can all have a beneficial effect.